Training on Processing Used Cooking Oil into "Environmentally Friendly Bright" Candles in Makmur Jaya Hamlet, Sangkima Village: Pelatihan Pengolahan Minyak Jelantah Menjadi Lilin “Terang Ramah Lingkungan” di Dusun Makmur Jaya Desa Sangkima - Nadzifah, Nauroh; Amalia Fauzia Rahma, Amalia; Putri, Resti Intan; Michael, Michael; Ambalinggi, Chrystofel; Wachyuni, Sucy; Ula, Siti Nikmatul; Aji, Bayu Purnama; Pratiwi, Anugrah; Shelomita, Shelomita; Kopalit, Dustin Hessel (ANDIL Mulawarman Journal of Community Engagement, 2026)
The community outreach and hands-on training program for producing eco-friendly candles from used cooking oil was conducted in Makmur Jaya Hamlet, Sangkima Village, South Sangatta District, East Kutai Regency. This activity aimed to raise public awareness of the health and environmental risks of used cooking oil and to provide practical skills with economic value. The implementation method consisted of three main stages: preparation, socialization, and practical training. The socialization stage delivered information on the dangers of repeated use of cooking oil and the environmental pollution caused by improper disposal. The practical stage involved refining used cooking oil and producing candles using paraffin wax, crayons, and essential oils. The results indicated increased community knowledge, enthusiastic participation—particularly from PKK women’s groups—and successful technical outcomes in candle production. This program not only provided educational benefits but also opened opportunities for creative, environmentally friendly businesses. In conclusion, the activity effectively enhanced environmental awareness and offered a practical solution for sustainable used cooking oil management